A new hope in the treatment of coronary vasospasm: bosentan - İlker Gül; Ahmet Çağrı Aykan; Tayyar Gökdeniz; Şükrü Çelik (KARE Publishing, 2013)
Atherosclerosis is the most important cause of acute coronary syndromes. The mediators that trigger vasospasm, including endothelin and serotonin, are synthesized and secreted into circulation from atherosclerotic plaques and surrounding tissues. A 68-year-old man was hospitalized due to acute coronary syndrome four times in a one-year period. The patient presented to emergency service again with heartburn and a pressure-like pain in his upper abdomen in February 2012. He was admitted to the coronary care unit with the detection of a more than three-fold increase in troponin values and ischemic changes on electrocardiography. By decision of the cardiology council, the endothelin receptor antagonist, bosentan was added to the treatment. There were no contraindications to this medication according to his blood and hepatic indicators. After confirmation of the Social Security Institution, bosentan was started as 62.5 mg twice a day. After the first month, the dose was increased to 125 mg b.i.d. As of completion of the eighth month of treatment with bosentan, the patient had not been hospitalized due to angina attack or acute coronary syndrome.